Organic functional group modified silicon negative electrode material and preparation method and application thereof
By modifying organic functional groups on the surface of silicon particles and forming an outer layer of conductive polymer, the volume expansion problem of the negative electrode material of silicon-based lithium-ion battery is solved when lithium is embedded, and the structural stability and high performance of the electrode are achieved.
Patent Information
- Application Number
- CN202411613306.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The negative electrode material of silicon-based lithium-ion battery will produce more than 300% volume expansion when fully embedded in lithium, resulting in structural powdering and degradation of electrode performance.
By modifying organic functional groups on the surface of silicon particles, pre-hydrolysis and in-situ polymerization are performed using silane coupling agent to form an outer layer of conductive polymer to alleviate volume expansion and stress accumulation.
It effectively alleviates the volume expansion of silicon particles, maintains the integrity and structural stability of the electrode, and improves the cycle stability and rate performance of lithium-ion batteries.
Smart Images

Figure CN119447253A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery negative electrode materials, and in particular to an organic functional group-modified silicon negative electrode material, a preparation method, and an application thereof. Background Art
[0002] Silicon-based lithium-ion battery anode materials have high specific capacity (~3579mAh g -1 ), low lithium insertion potential (~0.4V, Li + Silicon (Si) has attracted considerable research attention in recent years due to its wide availability of raw materials and its extensive lithium-ion battery technology. However, when fully embedded with lithium, Si expands by over 300%, generating significant stress and causing structural pulverization. This can lead to separation between the current collector and the active material on the negative electrode sheet, leading to rapid capacity decay. The fresh silicon surface exposed by the cracks creates more solid electrolyte interfaces at the electrode-electrolyte interface, consuming more electrolyte components and causing capacity decay with cycling. This intrinsic problem becomes more pronounced and severe with larger silicon particle size.
[0003] By coating the surface of silicon particles with inorganic materials, the problem of volume expansion of silicon materials when fully intercalated with lithium can be modified. The type and structural design of the coating material have an important influence on the performance of the silicon negative electrode. Carbon materials, such as amorphous carbon and graphite, are often used as three-dimensional protective coatings for silicon negative electrodes due to their excellent conductivity, chemical stability and mechanical strength. These carbon materials help to buffer the volume expansion of silicon during the charge and discharge process, while isolating the electrolyte and reducing side reactions, thereby improving the structural stability and electrochemical performance of the silicon negative electrode. In addition to carbon materials, metal oxides such as TiO2 and Al2O3 are also used as coating materials. These metal oxides have a certain rigidity, which can reduce side reactions between silicon and the electrolyte, inhibit volume expansion, and thus improve the cycle stability of the silicon negative electrode. However, while inorganic coatings can provide some protection, traditional rigid inorganic materials can crack and peel when silicon expands, rendering the protective layer ineffective. Cost and preparation complexity: Some inorganic coating materials for silicon anodes are expensive and complex to prepare, limiting their commercial application. Furthermore, the volume expansion of the silicon anode can restrict lithium-ion transport, impacting the battery's charge and discharge performance. Therefore, mitigating the volume expansion of silicon particles is a pressing technical challenge. Summary of the Invention
[0004] The present application provides a silicon negative electrode material modified with an organic functional group, a preparation method, and an application thereof, to solve the following technical problem: how to further alleviate the volume expansion of silicon particles.
[0005] In a first aspect, the present application provides a method for preparing a silicon anode material modified with an organic functional group, the method comprising:
[0006] pre-hydrolyzing the silane coupling agent to obtain a mixed solution;
[0007] adding a silicon material to the mixed solution to bond the silane coupling agent to the surface of the silicon material to obtain an intermediate; and
[0008] The intermediate, polymer monomer and initiator are polymerized in situ to form a conductive polymer on the surface of the intermediate to obtain a silicon negative electrode material.
[0009] Optionally, the mass of the silane coupling agent is 5% to 20% of the mass of the silicon material.
[0010] Optionally, the mass of the polymer monomer is 30% to 100% of the mass of the intermediate.
[0011] Optionally, the mass of the initiator is 1% to 5% of the mass of the polymer monomer.
[0012] Optionally, the silane coupling agent includes: γ-methacryloxypropyltrimethoxysilane.
[0013] Optionally, the polymer monomer contains a carbon-carbon double bond, and the polymer monomer includes one or more of vinylene carbonate, vinyl ethylene carbonate, polyethylene glycol diacrylate-based polymer, acrylamide-methylpropanesulfonic acid and 2,2,2-trifluoroethyl methacrylate.
[0014] Optionally, the silicon material is photovoltaic silicon waste, and the size of the photovoltaic silicon waste is 1 μm to 10 μm.
[0015] In a second aspect, the present application provides a silicon negative electrode material prepared by the method described in any one of the embodiments of the first aspect, wherein the silicon negative electrode material comprises:
[0016] A core, wherein the core is made of silicon material;
[0017] an intermediate layer, the intermediate layer being coated on the surface of the silicon material core, the intermediate layer being a hydrolyzed silane coupling agent; and
[0018] An outer layer, the outer layer covering the surface of the middle layer, the outer layer being a conductive polymer;
[0019] The inner core is bonded to the hydrolyzable functional group of the silane coupling agent after hydrolysis, and the outer layer is bonded to the non-hydrolyzable functional group of the silane coupling agent.
[0020] Optionally, the sum of the thicknesses of the intermediate layer and the outer layer is 0.5 nm to 5 nm.
[0021] In a third aspect, the present application provides a lithium battery, comprising the silicon negative electrode material described in the embodiment of the second aspect.
[0022] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0023] The present application provides a method for preparing a silicon negative electrode material modified with an organic functional group, the method comprising: pre-hydrolyzing a silane coupling agent to obtain a mixed solution; adding a silicon material to the mixed solution to bond the silane coupling agent to the surface of the silicon material to obtain an intermediate; and in situ polymerizing the intermediate, polymer monomer and initiator to form a conductive polymer on the surface of the intermediate to obtain a silicon negative electrode material. First, the silane coupling agent is hydrolyzed, and the hydrolyzable functional groups of the silane coupling agent will undergo a condensation reaction with the silanol groups on the surface of the photovoltaic silicon waste after hydrolysis to form a chemical bond. At the same time, the non-hydrolyzable functional group portion of the silane coupling agent remains on the surface of the silicon particles, providing polymerization sites for subsequent polymerization reactions; then, different organic functional group modifications are achieved through simple in situ polymerization. During the in situ polymerization process, the polymer network on the surface of the silicon particles can be cross-linked, and the confinement effect and stress dissipation during the particle expansion process can be achieved, thereby alleviating the huge volume expansion of the silicon particles and maintaining the integrity of the electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0025] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.
[0026] Figure 1 A schematic flow chart of a method for preparing an organic functional group-modified silicon anode material provided in an embodiment of the present application;
[0027] Figure 2 This is the SEM image of the photovoltaic silicon slag provided in Example 1 of the present application;
[0028] Figure 3 The SEM image and EDS mapping image of a single photovoltaic silicon slag provided in Example 1 of the present application;
[0029] Figure 4 The SEM image and EDS mapping image of a single silicon negative electrode material particle provided in Example 1 of the present application;
[0030] Figure 5 The C1s and F1s spectra of the XPS test of the photovoltaic silicon slag provided in Example 1 of this application;
[0031] Figure 6 The C1s and F1s spectra of the XPS test of the silicon negative electrode material provided in Example 1 of the present application;
[0032] Figure 7 FT-IR image of the silicon negative electrode material provided in Example 1 of the present application;
[0033] Figure 8 This is a battery cycle performance diagram of the silicon negative electrode material provided in Examples 1 and 7 to 11 of the present application;
[0034] Figure 9 This is a battery cycle performance diagram of the silicon negative electrode material provided in Examples 1 to 4 of the present application;
[0035] Figure 10 This is a battery cycle performance diagram of the silicon negative electrode material provided in Examples 1 and 6-7 of the present application;
[0036] Figure 11 This is a battery cycle performance diagram of the silicon negative electrode material provided in Example 1 of the present application;
[0037] Figure 12 This is a battery rate performance diagram of the silicon negative electrode material provided in Example 1 of the present application;
[0038] Figure 13 This is a full battery cycle performance diagram of the silicon negative electrode material provided in Example 1 of the present application. DETAILED DESCRIPTION
[0039] To make the purpose, technical solutions, and advantages of the embodiments of this application more clear, the technical solutions in the embodiments of this application will be clearly and completely described below in conjunction with the drawings in the embodiments of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of this application.
[0040] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a hard limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numbers within the range. For example, the description of a range from 1 to 6 should be considered to have specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which applies regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0041] In addition, in the description of the specification of this application, the terms "including", "comprising", etc. mean "including but not limited to". In this article, relational terms such as "first" and "second" are merely used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A and B can be singular or plural. In this article, "at least one" refers to one or more, and "plurality" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple. "Parts" such as parts by weight and parts by mass represent the proportional relationship between the components. In the proportional relationship involved in this article, the parameters that need to be described by proportion should be understood as the first term of the proportional formula in the order of description, and the proportional numbers should be understood as the second term of the proportional formula. For example, if the mass ratio of substance A, substance B, and substance C is 1:2:3, then substance A, substance B, and substance C should correspond one-to-one to the proportional numbers in the proportional formula in the order of description, that is, the mass of substance A: the mass of substance B: the mass of substance C = 1:2:3.
[0042] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0043] Figure 1 A schematic flow chart of a method for preparing an organic functional group-modified silicon negative electrode material provided in an embodiment of the present application.
[0044] See Figure 1 The present application provides a method for preparing a silicon negative electrode material modified with an organic functional group, the method comprising:
[0045] S1, pre-hydrolyzing the silane coupling agent to obtain a mixed solution;
[0046] In some embodiments, step S1 specifically includes: mixing a silane coupling agent, ethanol, and deionized water, and then adjusting the pH to 3-4 using acetic acid to perform the pre-hydrolysis.
[0047] The silane coupling agent is pre-hydrolyzed to allow the silane coupling agent to be more uniformly dispersed in the aqueous solution and to promote its hydrolysis reaction. During the pre-hydrolysis process, acetic acid is used to provide acidic conditions to promote the hydrolysis of the silane coupling agent.
[0048] In some embodiments, the silane coupling agent includes: γ-methacryloxypropyltrimethoxysilane.
[0049] γ-Methacryloxypropyltrimethoxysilane (containing) C=C-COO- can provide a double bond site for the subsequent polymerization reaction.
[0050] In some embodiments, the mass of the silane coupling agent is 5% to 20% of the mass of the silicon material.
[0051] The silane coupling agent is limited to 5% to 20% of the mass of the silicon material. This effectively forms a chemically bonded organic layer on the surface of the silicon material, thereby enhancing the compatibility and adhesion of the silicon material with other materials. This chemical bonding not only improves the overall performance of the composite material, such as mechanical strength, heat resistance, weather resistance, and chemical stability, but also reduces cracking and delamination during use. For example, the silane coupling agent can account for 5%, 7%, 9%, 10%, 12%, 15%, 18%, 20%, etc., of the mass of the silicon material.
[0052] S2, adding a silicon material to the mixed solution to bond the silane coupling agent to the surface of the silicon material to obtain an intermediate; and
[0053] Under the acidic conditions of acetic acid, the hydrolyzable functional groups of the silane coupling agent undergo a condensation reaction with the silanol (Si-OH) groups on the surface of the photovoltaic silicon waste, forming a chemical bond. Meanwhile, the non-hydrolyzable functional groups of the silane coupling agent remain on the surface of the silicon particles, providing polymerization sites for subsequent polymerization reactions. Thus, after modification with the silane coupling agent, sites are introduced on the surface of the silicon particles that can undergo polymerization reactions with polymer monomers terminated with different functional groups.
[0054] In some embodiments, the silicon material is photovoltaic silicon waste, and the size of the photovoltaic silicon waste is 1 μm to 10 μm.
[0055] Crystalline silicon wafers are the primary photoelectric conversion material in photovoltaic modules. With the development of photovoltaic energy storage, demand for crystalline silicon has surged. During the production process, 20% to 30% of the raw material is lost through steps such as diamond cutting, resulting in micron-sized silicon slag waste. Silicon slag waste cut with diamond wire contains minimal metallic impurities (such as Al, Fe, Ni, and Cr), making it unable to meet the high-purity silicon requirements for photovoltaic power generation. Consequently, it is either landfilled or subjected to energy-intensive remelting processes for reuse. However, silicon slag containing minimal metallic impurities can be recycled as anode material for lithium-ion batteries. Researchers studying the reuse of photovoltaic silicon slag have prepared a silicon-based anode material from high-quality photovoltaic silicon slag through ball milling and a two-step coating process. Surface coating with polyhexaazatriphenylene improves the performance of the silicon-based anode and optimizes the formation of the SEI film. Through rational electrolyte design, the micron-sized silicon from photovoltaic waste is reused in lithium-ion battery anodes, forming a flexible outer layer composed primarily of polymer and a rigid inner SEI rich in Li2O / LiF. Therefore, silicon slag waste is expected to be used as anode materials for silicon-based lithium-ion batteries.
[0056] Although photovoltaic silicon waste contains very small amounts of metallic impurities (such as Al, Fe, Ni, and Cr), these impurities have little impact on the performance of lithium-ion battery anode materials, making it suitable as a raw material for lithium-ion battery anode materials. This application utilizes photovoltaic silicon waste as a raw material for lithium-ion battery anode materials, enabling the recycling of waste materials, saving resources and reducing environmental pollution. Furthermore, using photovoltaic silicon waste as silicon material can reduce the production cost of lithium-ion battery anode materials.
[0057] S3. In-situ polymerizing the intermediate, polymer monomers and initiator to form a conductive polymer layer on the surface of the intermediate to obtain a silicon negative electrode material.
[0058] It should be noted that in-situ polymerization is a method of initiating a polymerization reaction directly in a dispersed phase. Reactive monomers (or soluble prepolymers of reactive monomers) and initiators can be added to the dispersed phase, allowing the polymerization reaction to occur in the dispersed core material. In this application, in-situ polymerization is carried out on the intermediate layer on the surface of the silicon material, forming an outer layer modified with organic functional groups and having an in-situ elastic network. This outer layer not only enhances the structural stability of the silicon anode material but also improves its electrochemical performance.
[0059] On the surface of the silicon particles, the sites modified with the hydrolyzed silane coupling agent undergo free radical polymerization with polymer monomers containing corresponding functional groups (such as methyl methacrylate and ethyl methacrylate). This polymerization reaction can occur in situ on the surface of the silicon particles, forming a dense polymer layer. As the polymerization reaction proceeds, the polymer chains continue to grow and intertwine on the surface of the silicon particles, ultimately forming an organic functional group-modified layer with an in situ elastic network. This elastic network layer can increase the flexibility and mechanical strength of the silicon anode, while also improving its wettability with the electrolyte and lithium ion conductivity.
[0060] In some embodiments, the mass of the polymer monomer is 30% to 100% of the mass of the intermediate.
[0061] The mass of the polymer monomer is limited to 30% to 100% of the mass of the intermediate, achieving cross-linking of the polymer network on the surface of the silicon particles. This achieves a confinement effect and stress dissipation during particle expansion, mitigates the significant volume expansion of the silicon particles, and maintains the integrity of the electrode. For example, the mass of the polymer monomer can be 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100%, etc., of the mass of the intermediate.
[0062] In some embodiments, the mass of the initiator is 1% to 5% of the mass of the polymer monomer.
[0063] Initiators play a crucial role in polymerization reactions, initiating chain reactions between monomers to form high-molecular-weight polymers. Limiting the initiator mass to 1% to 5% of the monomer mass can optimize polymerization rates, improve product quality, reduce production costs, and enhance environmental friendliness. Exemplary initiator mass ratios include 1%, 2%, 3%, 4%, 5%, and so on.
[0064] In some embodiments, the polymer monomer contains a carbon-carbon double bond, and the polymer monomer includes one or more of vinylene carbonate, vinyl ethylene carbonate, polyethylene glycol diacrylate-based polymer, acrylamido-methylpropanesulfonic acid, and 2,2,2-trifluoroethyl methacrylate.
[0065] In some embodiments, the initiator includes: azobisisobutyronitrile.
[0066] Compared with the existing technology, the present application discloses the preparation of a recycled silicon negative electrode material modified with different organic functional groups through simple in situ polymerization. By simply using acetic acid as a pH regulator, the hydrolysis reaction of KH570 and photovoltaic silicon slag in a water and ethanol system is controlled to achieve double bond modification, and then the modified double bonds are used as active sites to be in situ polymerized and coated with different functional groups with carbon-carbon double bonds. During the in situ polymerization process, the polymer network on the surface of the silicon particles can be cross-linked, thereby achieving the confinement effect and stress dissipation during the particle expansion process, alleviating the huge volume expansion of the silicon particles, and maintaining the integrity of the electrode. Unlike "rigid" inorganic materials, organic coatings have greater flexibility in withstanding large strains and volume changes, and the mechanical properties of organic coatings can be further adjusted by polymerization, branching or cross-linking; the organic layer can be designed with rich reactive groups to "bridge" with polymer adhesives or conductive polymers. These surface interactions can cause the interfacial adhesion between Si / adhesive / conductive polymer to be stronger than pure physical adhesion, which helps to maintain the integrity of the Si electrode; organic molecules containing Si-O / CO / CF bonds can coordinate with lithium ions, providing the possibility of guiding the rapid transport of lithium ions at the interface; they can be prepared through a synthetic route that does not involve complex equipment or high temperature and high pressure, and there is the possibility of scale-up process.
[0067] Based on a general inventive concept, the present application provides a silicon negative electrode material prepared by the method described in any one of the above embodiments, wherein the silicon negative electrode material comprises:
[0068] A core, wherein the core is made of silicon material;
[0069] an intermediate layer, the intermediate layer being coated on the surface of the silicon material core, the intermediate layer being a hydrolyzed silane coupling agent; and
[0070] An outer layer, the outer layer covering the surface of the middle layer, the outer layer being a conductive polymer;
[0071] The inner core is bonded to the hydrolyzable functional group of the silane coupling agent after hydrolysis, and the outer layer is bonded to the non-hydrolyzable functional group of the silane coupling agent.
[0072] Core: The core is made of silicon, an ideal material for lithium-ion battery negative electrodes, offering high specific capacity and energy density. However, the lithium insertion / delithiation process is often accompanied by significant volume changes, leading to problems such as pulverization of the active material and the continuous formation of the solid electrolyte interface (SEI). Therefore, silicon materials need to be modified to improve their cycling stability and safety. Intermediate layer: The intermediate layer is a hydrolyzed silane coupling agent. A silane coupling agent is a compound with two distinct functional groups: one that can chemically react with the surface of the silicon material to form a chemical bond; the other can chemically react with organic materials such as conductive polymers. By hydrolyzing the silane coupling agent, it can form a chemical bond with the surface of the silicon core, thereby strengthening the connection between the core and the outer layer. Outer layer: The outer layer is a conductive polymer, a novel electrode material that can improve the conductivity and cycle life of lithium-ion batteries. By coating the surface of the silicon core and intermediate layer, the conductive polymer forms a protective layer, preventing direct contact between the silicon material and the electrolyte during charge and discharge, thereby reducing the occurrence of side reactions. At the same time, the conductive polymer can also improve the overall conductivity of the silicon negative electrode material, facilitating the rapid transmission of lithium ions.
[0073] In some embodiments, the sum of the thicknesses of the intermediate layer and the outer layer is 0.5 nm to 5 nm.
[0074] Limiting the combined thickness of the middle and outer layers to 0.5 nm to 5 nm ensures sufficient mechanical strength and stability for the silicon anode material without adding excessive mass or volume, thus maintaining the lightweight and high energy density of lithium-ion batteries. For example, the combined thickness of the middle and outer layers can be 0.5 nm, 1 nm, 1.5 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, etc.
[0075] The silicon negative electrode material is realized based on the preparation method of the above-mentioned silicon negative electrode material. The specific steps of the preparation method of the silicon negative electrode material can refer to the above-mentioned embodiment. Since the silicon negative electrode material adopts part or all of the technical solutions of the above-mentioned embodiment, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be repeated here one by one.
[0076] The present application provides a lithium battery, which includes the silicon negative electrode material described in the above embodiment.
[0077] The present application will be further described below in conjunction with specific examples. It should be understood that these examples are intended to illustrate the present application only and are not intended to limit the scope of the present application. The experimental methods in the following examples where specific conditions are not specified are generally measured according to industry standards. If there are no corresponding industry standards, then the methods are carried out according to general international standards, conventional conditions, or the conditions recommended by the manufacturer.
[0078] Example 1
[0079] This embodiment provides a method for preparing a recycled silicon negative electrode material modified with different organic functional groups by simple in-situ polymerization. The specific method comprises the following steps:
[0080] Step 1: Weigh 0.3 g KH570, 24 ml ethanol, and 8 ml deionized water into a round-bottom flask, place on a magnetic stirrer and mix for 30 minutes, add acetic acid, adjust the pH to 3-4, and pre-hydrolyze at room temperature for 12 hours.
[0081] Step 2: Weigh 2.0 g of industrial micronized silicon slag in a mortar and grind thoroughly until there are no agglomerated particles. Then transfer the slag to a pre-hydrolyzed round-bottom flask and add 1 ml of acetic acid. Ultrasonic dispersion is performed for 30 minutes. After ultrasonic dispersion, the round-bottom flask is transferred to a preheated 60°C oil bath at 300 rpm. Hydrolysis is carried out in a sealed system for 10 hours. After the reaction is completed, the solid and liquid are separated by vacuum filtration. The filter cake is washed three times with 80 ml of anhydrous ethanol and then deionized water. The solid is collected and pre-dried in a 60°C forced air oven. It is then transferred to an 80°C vacuum oven to dry. This is referred to as intermediate Si@KH570.
[0082] Step 3: Weigh 0.5g of the intermediate Si@KH570 in a mortar and grind thoroughly. The mixture is then transferred to a round-bottom flask and 25ml of N,N-dimethylformamide is added. 0.25g of trifluoroethyl methacrylate (TFEMA) and 0.0075g of azobisisobutyronitrile are then added to the solution. Mix the mixture for 30 minutes with a magnetic stirrer. Then, purge the mixture with high-purity nitrogen for 30 minutes to remove oxygen from the solvent. After purging, seal the mixture and ultrasonically disperse it for 30 minutes. The mixture is then transferred to a 60°C oil bath and allowed to react for 24 hours. After the reaction, the solid and liquid are separated by vacuum filtration. The filter cake is then washed three times with 80ml of anhydrous ethanol and then deionized water. The solid is collected and pre-dried in a 60°C forced air oven before being dried in a vacuum oven at 80°C. The resulting solid product is designated Si@TFEMA.
[0083] Example 2
[0084] The difference between this embodiment and embodiment 1 is that the added mass of KH570 is 0.1 g.
[0085] Example 3
[0086] The difference between this embodiment and embodiment 1 is that the added mass of KH570 is 0.2 g.
[0087] Example 4
[0088] The difference between this embodiment and embodiment 1 is that the added mass of KH570 is 0.4 g.
[0089] Example 5
[0090] The difference between this embodiment and embodiment 1 is that the mass of trifluoroethyl methacrylate added is 0.15 g.
[0091] Example 6
[0092] The difference between this embodiment and embodiment 1 is that the mass of trifluoroethyl methacrylate added is 0.5 g.
[0093] Example 7
[0094] The difference between this embodiment and embodiment 1 is that the polymer monomer is pentaerythritol tetraacrylate (PENTA).
[0095] Example 8
[0096] The difference between this embodiment and embodiment 1 is that the polymer monomer is vinylene carbonate (VC).
[0097] Example 9
[0098] The difference between this embodiment and embodiment 1 is that the polymer monomer is 2-acrylamido-2-methylpropanesulfonic acid (AMPS).
[0099] Example 10
[0100] The difference between this embodiment and embodiment 1 is that the polymer monomer is vinyl carbonate (VEC)
[0101] Example 11
[0102] The difference between this embodiment and embodiment 1 is that the polymer monomer is polyethylene glycol diacrylate-based polymer (PEGDA700).
[0103] Example 12
[0104] The Si@TFEMA powder prepared in Examples 1-11, acetylene black, and polyacrylic acid (PAA) were uniformly mixed in N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1. The resulting slurry was then coated on copper foil and the NMP solvent was dried under vacuum at 80°C. The resulting electrode was cut into 10 mm discs and assembled with a lithium metal counter electrode into CR2032 button cells for subsequent electrochemical performance testing.
[0105] Figure 2 This is the SEM image of photovoltaic silicon slag provided in Example 1 of this application. Figure 2 It can be seen that the size distribution of photovoltaic silicon slag is 1μm to 10μm.
[0106] Figure 3 The SEM image and EDS mapping image of a single photovoltaic silicon slag provided in Example 1 of this application. Figure 3 It can be seen that there is no F element distribution on the surface of photovoltaic silicon slag raw material particles.
[0107] Figure 4 The SEM image and EDS mapping image of a single silicon negative electrode material particle provided in Example 1 of the present application. Figure 4 It can be seen that the F element concentration on the surface of the modified particles is significantly increased.
[0108] Figure 5 The C1s and F1s spectra of the XPS test of photovoltaic silicon slag provided in Example 1 of this application are shown in FIG. Figure 5 It can be seen that no characteristic peak of F element was detected on the surface of the unmodified material.
[0109] Figure 6 The C1s and F1s spectra of the XPS test of the silicon negative electrode material provided in Example 1 of the present application are shown in FIG. Figure 6 It can be seen that the characteristic peaks of -CF3 / -CF2 / -CF and -C=O of TFEMA in C1s and F1s can be detected on the surface of Si@TFEMA material.
[0110] Figure 7 This is the FT-IR image of the silicon negative electrode material provided in Example 1 of the present application. Figure 7 It can be seen that the characteristic peaks from the polymer monomer TFEMA are all detected on the coated materials.
[0111] A series of characterizations show that after coating, using trifluoromethyl ethyl acrylate (TFEMA) as a second coating structure, it is recorded as Si@TFEMA. The characteristic peak of -CF3 in Fourier infrared testing (1150-1170cm-1) can be detected on the surface of silicon particles, and the characteristic peak of -CF3 in X-ray photoelectron spectroscopy (XPS) (293eV), which can indicate that the surface particles contain a trifluoromethyl-terminated TFEMA layer. Atomic force microscopy (AFM) testing shows that the Young's modulus of the electrode before and after coating has changed, increasing from 603Mpa to 705Mpa. The polymer network achieves self-crosslinking on the surface of the silicon particles, forming a layer of elastic coating network, which realizes the volume confinement and stress dissipation of the silicon particles.
[0112] Figure 8This is a battery cycle performance diagram of the silicon negative electrode material provided in Examples 1 and 7 to 11 of this application. Figure 8 It can be seen that materials terminated with different functional groups can also improve the cycle performance of silicon negative electrode materials to a certain extent.
[0113] Figure 9 This is a battery cycle performance diagram of the silicon negative electrode material provided in Examples 1 to 4 of this application. Figure 9 It can be seen that when the mass of KH570 is 5% to 20% of the mass of photovoltaic silicon slag, the cycle performance of silicon negative electrode materials can be improved to a certain extent. When the mass of KH570 is 15% of the mass of photovoltaic silicon slag, it is the optimal embodiment.
[0114] Figure 10 This is a battery cycle performance diagram of the silicon negative electrode material provided in Examples 1 and 6-7 of this application. Figure 10 It can be seen that when the mass of trifluoroethyl methacrylate is 30% to 100% of the mass of the intermediate, the cycle performance of the silicon negative electrode material can be improved to a certain extent. The optimal embodiment is when the mass of trifluoroethyl methacrylate is 50% of the mass of the intermediate.
[0115] Figure 11 This is a battery cycle performance diagram of the silicon negative electrode material provided in Example 1 of this application. Figure 11 The organic elastic layer significantly improves the long-term cycling performance of the silicon electrode. After 364 cycles at a current density of 1 A / g, the charge capacity reached 1646.75 mAh / g, with a cycle retention rate of 70.02%, compared to only 35.77% for the comparison sample, photovoltaic silicon slag.
[0116] Figure 12 This is a graph showing the battery rate performance of the silicon negative electrode material provided in Example 1 of this application. Figure 12 The Si@TFEMA electrode exhibits significantly improved capacity at high current densities compared to the silicon slag electrode. At 10 A / g, the Si@TFEMA electrode can achieve 500 cycles, while the capacity of the comparison sample, photovoltaic silicon slag, rapidly decays to 100 mAh / g after 50 cycles.
[0117] Figure 13 This is a full battery cycle performance diagram of the silicon negative electrode material provided in Example 1 of this application. Figure 13 The Si@TFEMA electrode exhibits superior capacity retention within a full battery system. When assembled with commercial lithium iron phosphate into a button-type full battery, it can stably cycle 100 times at 0.2C, demonstrating the material's practical value.
[0118] In addition, one or more technical solutions in the embodiments of the present application have at least the following technical effects or advantages:
[0119] In the embodiments of the present application, different organic functional groups are modified by simple in situ polymerization and coated on the surface of silicon particles, thereby improving the interface and bulk structure of silicon, and constructing an in situ polymer network to alleviate the intrinsic volume expansion problem of silicon.
[0120] In the examples of this application, the modification of different organic groups on the surface of silicon particles is achieved through a simple solution hydrolysis and in-situ polymerization two-step liquid phase chemical reaction. The preparation method is simple, highly reproducible, and easy to post-process. The surface-modified functional groups can achieve a stable solid electrolyte phase interface of the silicon negative electrode, and the in-situ polymer network can maintain the integrity of the particles, achieving excellent cycle and rate performance. At the same time, the trifluoromethyl-modified silicon particles can effectively adsorb components in the electrolyte and controllably form an SEI. The material has excellent electrochemical cycle performance and rate performance.
[0121] In the examples of this application, the thickness and degree of polymerization of the coating layer can be varied by adjusting the ratio of KH570, the ratio of TFEMA, the hydrolysis time, and the pH value. The present invention is not limited to TFEMA as the sole end-capping monomer, and the organic molecule coating can be achieved by in-situ polymerization with double-bond-modified silicon particles.
[0122] The foregoing is merely a list of specific embodiments of the present application, intended to enable those skilled in the art to understand or implement the present application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application is not limited to the embodiments shown herein, but is intended to conform to the broadest scope consistent with the principles and novel features of the present application.
Claims
1. A method for preparing a silicon negative electrode material modified with an organic functional group, the method comprising: pre-hydrolyzing the silane coupling agent to obtain a mixed solution; Adding silicon material to the mixed solution to bond the silane coupling agent to the surface of the silicon material to obtain an intermediate; as well as The intermediate, polymer monomer and initiator are polymerized in situ to form a conductive polymer on the surface of the intermediate to obtain a silicon negative electrode material.
2. The method according to claim 1, characterized in that The mass of the silane coupling agent is 5% to 20% of the mass of the silicon material.
3. The method according to claim 1, characterized in that The mass of the polymer monomer is 30% to 100% of the mass of the intermediate.
4. The method according to claim 1, characterized in that: The mass of the initiator is 1% to 5% of the mass of the polymer monomer.
5. The method according to claim 1, characterized in that The silane coupling agent includes: γ-methacryloxypropyltrimethoxysilane.
6. The method according to claim 1, characterized in that The polymer monomer contains a carbon-carbon double bond, and the polymer monomer includes one or more of vinylene carbonate, vinyl carbonate, polyethylene glycol diacrylate-based polymer, acrylamide-methylpropanesulfonic acid and 2,2,2-trifluoroethyl methacrylate.
7. The method according to claim 1, characterized in that The silicon material is photovoltaic silicon waste, and the size of the photovoltaic silicon waste is 1 μm to 10 μm.
8. A silicon negative electrode material prepared by the method according to any one of claims 1 to 7, characterized in that: The silicon negative electrode material comprises: A core, wherein the core is made of silicon material; An intermediate layer, the intermediate layer is coated on the surface of the silicon material core, and the intermediate layer is a hydrolyzed silane coupling agent; and An outer layer, the outer layer is coated on the surface of the middle layer, and the outer layer is a conductive polymer; The inner core is bonded to the hydrolyzable functional group of the silane coupling agent after hydrolysis, and the outer layer is bonded to the non-hydrolyzable functional group of the silane coupling agent.
9. The silicon negative electrode material according to claim 8, characterized in that: The sum of the thickness of the intermediate layer and the outer layer is 0.5 nm to 5 nm.
10. A lithium battery, characterized in that: The lithium battery comprises the silicon negative electrode material described in claim 8 or 9.
Citation Information
Patent Citations
Preparation method for negative electrode active material of lithium ion battery
CN103474666A
Silicon-base negative material with silane coupling agent and conductive polymer two-layer cladding structure as well as preparation method and application of material
CN103996834A
Composite nano-silicon negative electrode and preparation and application thereof
CN111883760A
Silicon negative electrode material and preparation method thereof, negative electrode plate and electrochemical device
CN117976878A
Cited By
Coating modification method of negative electrode material, negative electrode material and application of negative electrode material
CN120048882A
Conductive polymer coated photovoltaic waste silicon material, preparation method thereof and lithium battery
CN122177790A